STRATEGI PEMBELAJARAN UNTUK MENGEMBANGKAN KARAKTER CINTA TANAH AIR ANAK USIA 5-6 TAHUN TK BRUDER PONTIANAK - Een Devina; Marmawi Marmawi; Desni Yuniarni (Universitas Tanjungpura, 2019)
AbstractThe aim of this research is to know learning strategies that used by the teacher to develop the patriotism character in children aged 5-6 years in Bruder Kanisius Kindegarten Nort Pontianak. Research method that used is descriptive with the type of qualitative research. The source of the data for the research is one teacher from B4 group Bruder Kanisius Kindergarten. Technique of the research is observation with instrument observation sheet, interview with instrument inteview sheet and documentary with instrument documentation. Analysis data for this research is collection the data, reduction the data, presentation and conclusion/verification. Based on the result of the research that have been done and from the result from data analysis, in general it can be conclude that the teacher have been applied introduction activity learning, delivery the information, involve the participation from the student and do some test like question and answer to the student, but it still looks like there are many student who do not have love for their motherland, there are still many children who do not love the physical environment of the Indonesian such as littering, do not know the national holidays such as Kartini’s Day, National Education Day, Teacher’s Day, Proclamation, the birth of Pancasila.Key Words: Learning Strategies, Love the Motherland